Exploring the relationship between mindfulness and burnout among preschool teachers: the role of dispositional equanimity and empathy - He, Yuanqing; Wang, Xin; Wang, Xiaqing; Li, Xiaowen (Frontiers in Psychology, 2024)
The objective of this study is to delve into the underlying mechanisms between mindfulness and burnout among preschool teachers. Employing a cross-sectional research design, this study surveyed 1,980 Chinese preschool teachers using the Mindful Attention Awareness Scale (MAAS), Preschool Teacher Dispositional Equanimity Questionnaire (PTDEQ), Empathy Scale (ME), and Maslach Burnout Inventory for Educators (MBI-ES). The results revealed a significant negative correlation between preschool teachers’ mindfulness and burnout. A mediation analysis demonstrated that dispositional equanimity served as a mediator between mindfulness and preschool teacher burnout. Furthermore, a moderation analysis indicated that empathy moderated the influence of dispositional equanimity on preschool teacher burnout. These findings suggest that mindfulness can enable preschool teachers to better cope with workplace challenges with a more peaceful mindset.